(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2025)
ABSTRACT Convergence is one of the government’s programs to prevent stunting. Stunting cases at the Tugu Mulyo Community Health Center are currently 1.52%. Tugu Mulyo Community Health Center has implemented stunting convergence but the results are still not optimal. The research aims to obtain in-depth information about the role of Community Health Centers in convergence efforts to prevent stunting at Tugu Mulyo Community Health Center based on input, process and output components. The research is qualitative research through data collection by interviews, documents and observations. The research was carried out from 03-18 June 2024 and was carried out at the Tugu Mulyo Community Health Center. Data collection techniques using in-depth interviews with informants (in-depth interviews). The informants in the research were 8 people from the Community Health Center. The research triangulation used is sources, techniques and time. Data collection in this research was in-depth interviews, observation and document review. The results show that there is one nutrition worker, the source of funds for stunting comes from operational assistance for health centers, the infrastructure used is appropriate, namely anthropometry, and cross-sector collaboration has been carried out in efforts to prevent stunting at the Tugu Mulyo Community Health Center. Based on the research results, it was concluded that the role of Community Health Centers in preventing stunting is still not optimal. Community Health Centers can optimize the role of cross-sectors that are part of the implementation of convergence in Lempuing sub-district in accordance with the tasks and functions of these cross-sectors.